ANALISIS PENGARUH CAPITAL/LABOUR INTENSIVE, INVESTASI, KEPEMILIKAN MANAJERIAL, LEVERAGE OPERASI DENGAN VARIABEL MEDIASI KEBIJAKAN DIVIDEN DAN LEVERAGE KEUANGAN TERHADAP NILAI PERUSAHAAN - Robi Nugraha (LPPM Universitas Negeri Jakarta, 2018)
ABSTRACT The purpose of this study was to analyze the influence of capital labour intensive, investment, managerial ownership, operating leverage, dividen and financial leverage on the firm value of Indonesia non financial sector companies, the influence of capital labour intensive, investment, managerial ownership, operating leverage variable on dividen and financial leverage of Indonesia non financial sector companies, and the influence of capital labour intensive, investment, managerial ownership, operating leverage variable on the firm value through dividen and financial leverage as intervening variable. The research data was collected using purposive sampling method to the data of non financial sector companies listed on the Indonesian Stock Exchange during the period 2003-2012. Based on the criteria of the study obtained 310 samples were then analyzed Using the panel data regression and path analysis. The results show that the capital labour intensive, investment, managerial ownership, operating leverage, dividen and financial leverage have significant influences on the firm value of Indonesia non financial sector companies. The capital labour intensive, investment, managerial ownership, operating leverage variable do not have significant influences on dividen. The capital labour intensive, investment, managerial ownership, operating leverage variable have significant influences on financial leverage. With path analysis, the result show the The capital labour intensive, investment, managerial ownership, operating leverage variable do not have significant influence on the firm value of Indonesia non financial sector companies with dividen and financial leverage as intervening variable. Keywords: Capital Labour Intensive, Investment, Managerial Ownership, Operating Leverage, Dividen and Financial Leverage, Firm Value.